Effect of water warming on the structure of biofilm-dwelling communities. (October 2020) - Majdi, Nabil; Uthoff, Jana; Traunspurger, Walter; Laffaille, Pascal; Maire, Anthony
Graphical abstract: Highlights: We tested the effects of in situ water warming on river biofilm communities. The biomass of algae and invertebrates was similar between thermal conditions. Cyanobacteria and nematodes were relatively favoured at heated site. Nematode taxonomic and functional diversity was greater at heated site. Biofilm community changes may be potential bio-indicator of warming. Abstract: Water warming, either resulting from global or local drivers, is of growing concern for aquatic environments. Changes in thermal regimes may alter the functioning and the trophic dynamics of river ecosystems as most aquatic biota like micro-algae, invertebrates, or fish are poikilotherms. Because biofilms integrate basal and intermediate components of aquatic food webs, examination of their responses to warming should contribute to a better understanding of the effects of ongoing climate change on river ecosystems. In this study, we considered sites that were or were not exposed directly to thermal effluents from a nuclear power plant as " in situ laboratories" of the effect of climate change and water warming. To compare the structure of algal and invertebrate communities dwelling in epilithic biofilms subjected to different thermal regimes in the Garonne River, sets of concrete tiles were placed in the river and the biofilm growing on these standard substrates was sampled after two months of colonisation. The site located within the thermal plume directly downstream of the thermal effluents showed warmer average water temperature (mean ΔT of about 1.5 °C over the study period) and greater daily temperature fluctuations in comparison to the control site. Algal and invertebrate biomass did not differ significantly, but the structure of communities differed markedly between sites. At the heated site, the proportion of cyanobacteria was higher, while there were fewer micro-crustaceans and larvae of insects and bivalves. However, the population of chironomids showed a greater proportion of relatively large individuals. Interestingly, nematodes were more abundant, and their communities comprised more species at the heated site. Their feeding-types were also more diverse showing a greater proportion of algivores, large-sized omnivorous and predatory species. Changes in the abundance and age structure further showed that some bacterivore species, such as Eumonhystera vulgaris, thrived especially well at the heated site, whereas another bacterivore, Monhystrella paramacrura, thrived well at the control site. In the context of climate change, our results highlight that warmer and more fluctuating water temperatures have the potential to alter the body-size spectrum, species composition, distribution of feeding specialisations and age structure within biofilm-dwelling communities.